Statistical analysis of regional STEC gradient trends for midlatitude ionosphere - Meltem Koroglu; Feza Arikan (Geodesy and Geodynamics)
In this study, the gradients of Total Electron Content (TEC) for a midlatitude region are estimated and grouped with respect to the distance between neighboring stations, time periods within a day, and satellite directions. Annual medians of these gradients for quiet days are computed as templates. The metric distances (L2N) and Symmetric Kullback-Leibler Distances (SKLD) are obtained between the templates and the daily gradient series. The grouped histograms are fitted to the prospective Probability Density Functions (PDF). The method is applied to the Slant Total Electron Content (STEC) estimates from the Turkish National Permanent GPS Network (TNPGN-Active) for 2015. The highest gradients are observed in the east-west axis with a maximum of 25 mm/km during a geomagnetic storm. The maximum differences from the gradient templates occur for neighboring stations within 100–130 km distance away from each other, during night hours, and for regions bordering the Black Sea and the Mediterranean in the northeast and southeast of Turkey. The empirical PDFs of the station-pair gradients are predominantly Weibull-distributed. The mean values of Weibull PDFs in all station groups are between 1.2 and 1.8 mm/km, with an increase during noon and afternoon hours. The standard deviations of the gradient PDFs generally increase during night hours. The algorithm will form a basis for quantifying the stochastic variations of the spatial rate of change of TEC trends in midlatitude regions, thus supplementing reliable and accurate regional monitoring of ionospheric variability.